Length-weight relationship and condtion factor of Heterobranchus lingifilis Valenciennes, 1840, reared in tank and earthen ponds - Pepple, P.C.G. (2019)
Length-weight relationship and condition factor of Heterobranchus longifilis Valenciennes, 1840, reared in fibre-glass tanks and earthen ponds at the Nigerian Institute for Oceanography and Marine Research Lagos, Nigeria, were studied. Fish were stocked at a density of 20 fish.m¯² in triplicate 25m² ponds fertilised with chicken droppings and hay, and 250 fish.m-³ in triplicate 2m³ fibre-glass tanks. The fish were fed with pelleted feed of 42% crude protein, at a mean rate of 1.3% fresh body weight thrice daily for 6 months. At the end of 6 months of culture, 30 H. longifilis were sampled from each replicate. They were weighed and total length measured. Fish reared in tanks had a mean length of 30.3±0.5cm and a mean weight of 1,344±155g. Fish reared in ponds had a mean length of 32.6±1.5cm and a mean weight of 1,360±40.6g. Mean “k” value was 1.63±0.12 and 1.5±0.02 in tanks and ponds respectively. Mean “b” values were lower in tanks at 2.88±0.2 in comparison with 3.047±0.015 obtained for ponds, indicating negative and positive allometry respectively. The length–weight relationship of H. longifilis reared in tanks and ponds showed positive correlation (r = 0.99).